Evaluation of growth, yield and quality of maize as influenced by genotypes and nitrogen levels (Bangladesh Journal of Botany, 2014)
Among genotypes, Dekalb 900 M Gold recorded significantly higher dry matter/plant, LAI, cobs placement height, grain yield, nitrogen content, protein content, protein yield and protein productivity than other genotypes. Leaves/plant and phytosynthetically active radiation (PAR) above canopy did not influenced by genotypes. Dry matter/plant, plant height, LAI, cobs placement height, protein content, protein yield and protein productivity exhibited higher under highest levels of nitrogen (160 kg N/ha), but at par with 120 kg N/ha. However, grain yield (6300 kg/ha) was highest under nitrogen levels of 120 kg/ha, but also at par with 160 kg N/ha (6240 kg/ha). The effect of applied nitrogen was found non-significant in respect of leaves/plant, PAR above and below canopy, photosynthetically active radiation interception and days taken to tasseling and silking. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19747 Bangladesh J. Bot. 43(1): 59-64, 2014 (June)